1988
DOI: 10.1159/000167618
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte Sedimentation Rate in Glomerular Disease: Association with Urinary Protein

Abstract: The erythrocyte sedimentation rate (ESR) correlated significantly with the total urinary protein (TUP) in 24-hour urine collections in patients with glomerular disease (p < 0.05 to p < 0.001). The relationship was linear for all patients with a glomerular process but no longer held true once the patients were treated with immunosuppressives, or when the underlying disease excluded the glomerulus. The association between ESR and TUP was generally of the magnitude ESR = TUP X 10. ESR was not correlated with crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…These findings have already been shown in previous studies [1-7, 9-12, 15]. The results in the present study confirmed the finding of Liverman et al [15] who recently found a direct association of ESR with urine protein excretion in glomerular disease. With institution of ste roid therapy, FDP started to decrease, and platelet count, a2M, ATI II, Pig, a2AP and protein C started to increase despite unchanged nephrotic state from that before ste roid therapy, in remission induced by steroids, these changes were held except for ESR, fibrinogen and FDP which normalized during off-steroid therapy.…”
Section: Discussionsupporting
confidence: 94%
“…These findings have already been shown in previous studies [1-7, 9-12, 15]. The results in the present study confirmed the finding of Liverman et al [15] who recently found a direct association of ESR with urine protein excretion in glomerular disease. With institution of ste roid therapy, FDP started to decrease, and platelet count, a2M, ATI II, Pig, a2AP and protein C started to increase despite unchanged nephrotic state from that before ste roid therapy, in remission induced by steroids, these changes were held except for ESR, fibrinogen and FDP which normalized during off-steroid therapy.…”
Section: Discussionsupporting
confidence: 94%
“…The mechanism(s) possibly associated with the increased fibrinogen production in type 2 diabetes have been previously discussed in detail [20,21,35], and may include insulin resistance, hyperglucagonaemia, increased fibrinogen degradation products acting as stimulators of fibrinogen production in the liver, and possibly, also a subclinical inflammatory state otherwise not detectable by standard assays. In our albuminuric type 2 diabetes patients, the increased ESR, which is a common finding in albuminuria [36], may indicate the occurrence of a mild inflammatory state, despite the normality of other biochemical (leucocyte counts, urinalysis, α 2 -globulins) and clinical indices of inflammation, with the exception of a mild, albeit insignificant, increase of CRP. Therefore, in addition to the previously mentioned factors, a subclinical inflammatory condition, with the associated expected changes in inflammatory cytokines (that were not measured in this study), may represent a stimulus towards increased fibrinogen production.…”
Section: Discussionmentioning
confidence: 61%
“…In addition, tumor lysis syndrome can cause uric acid nephropathy as well as crystal arthropathy. Finally, end-stage renal disease and proteinuria cause an elevated erythrocyte sedimentation rate, which should not be suspected as active rheumatic disease or occult malignancy [37,38]. …”
Section: Renal and Rheumatic Manifestations Of Other Systemic Diseasesmentioning
confidence: 99%